Analisa Sistem Informasi Akuntansi Penjualan di PT. Yapindo Transportama : PCP EXPRESS Surabaya - Tasya Tifany Aulia; Agus Subandoro (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Every company will need a sales information system for a business due to increased effectiveness in competitive advantage by adding to the products and services it produces. In addition, the company's sales information system is very influential because the company will later need this information for its operations for decision making, calculating basic costs, and so on. Therefore, the objectives to be achieved in this study are (1) to find out the problems of the accounting system run by the company, and (2) to find out the sales accounting information system at PCP Express Surabaya, both cash sales and invoices/credits. From the results of the analysis carried out, it can be locked that: (1) PCP Express Surabaya already has a computer-based accounting system for cash/cash sales and invoices/credits, and (2) problems in the implementation of cash sales accounting systems that still require development, (3) Internal control at PCP Express Surabaya is quite good because of the implementation of application and segregation of duties.